Perancangan Buku Komik City Guide Pariwisata Kota Surabaya Berbasis Ilustrasi Digital Guna Menganalkan Wisata Surabaya - Anugerah, Otto Archio Putra; Budiardjo, Hardman; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2016)
The purpose of the design a comic book City Surabaya tourism guide is to introduce and promote tourism. Further research is done using qualitative research methodsthat do interviews, observation, and literature to obtain data that is used in the creation of design concepts to support the comic book city Surabaya tourism guide. The data were analyzed by using multiple stage, apply the reduction of data, data presentation, and conclusion. After analyzing the data, the found discuss the design concepts or keywords